2008
DOI: 10.1088/0022-3727/41/24/245004
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and magnetic properties of Ga1−xMnxN films grown by MOCVD

Abstract: This paper reports the impact of the Mn incorporation on the structural and magnetic properties of Ga 1-x Mn x N on the metal-organic vapor phase deposition (MOCVD). Crystalline quality and phase purity were determined by high-resolution X-ray diffraction and indicated that no macroscopic second phases are formed during growth. Atomic force microscopy revealed a 2-dimensional MOCVD step-flow growth pattern in the Mn-incorporated samples. Various annealing steps were applied to some of the samples to reduce com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The CL spectrum shows the progressive reduction in intensity of band-edge luminescence with increasing Co concentration. The decrease in the intensity of band-edge luminescence with Co doping seems to be due to the presence of traps or defect states in the band gap originated by the doping of Co (Yang et al 2008;Lvill et al 2008). The band at 3.263 eV for undoped and the bands at 3.21 eV for Co-doped GaN were observed, these emissions were also identified by previous authors and assigned as donor-acceptor pair emission (DAP) for doped and undoped GaN (Lagerstedt and Monemar 1974;Loan et al 2009).…”
Section: Cathodoluminescencesupporting
confidence: 68%
“…The CL spectrum shows the progressive reduction in intensity of band-edge luminescence with increasing Co concentration. The decrease in the intensity of band-edge luminescence with Co doping seems to be due to the presence of traps or defect states in the band gap originated by the doping of Co (Yang et al 2008;Lvill et al 2008). The band at 3.263 eV for undoped and the bands at 3.21 eV for Co-doped GaN were observed, these emissions were also identified by previous authors and assigned as donor-acceptor pair emission (DAP) for doped and undoped GaN (Lagerstedt and Monemar 1974;Loan et al 2009).…”
Section: Cathodoluminescencesupporting
confidence: 68%
“…The further evidences of these type defects were also observed by the Raman spectroscopy and calthodoluminescence spectroscopy in our previous work. 14,26 With increasing the Mn concentration, the V N or V N related complex are formed and result in forming the local vibrational mode and the energy level observed by the Raman and calthodoluminescence spectroscopy respectively. The V N -Mn Ga complex is predicated to have low formation energies and is very stable when the Fermi level is at midgap of GaN.…”
mentioning
confidence: 99%
“…We demonstrated that the ferromagnetism decline of the film could be attributed to the valence state variation from Mn +3 to Mn +2 induced by electron compensation with Fermi level rising after Si co-doping. And, this resulted in t 2 state of Mn, deemed to be related to ferromagnetism origin via the double-exchange interaction in our previous works [32][33][34], being totally occupied. Then, we discuss the corresponding results about the electrical property of sample S 2 .…”
Section: Resultsmentioning
confidence: 86%